Penggunaan Biji Wijen, Kecipir dan Jagung Sebagai Media Pembibitan Jamur Tiram Putih (Pleurotus ostreatus) - Pangeran Andareas Panggabean; Lia Rahayu; Kuat Watini; Burhannudin Burhannudin; Indah Wahyuningsih (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The purpose of this study was to determine the optimal medium for nursery of White Oyster mushroom (Pleurotus ostreatus). The nursery media used in this study were Sesame, Winged Bean and Corn seeds. The parameter measured was the growth of P. ostreatus mycelium per two days for 14 days of incubation. The design of this study used a Completely Randomized Design (CRD) with 3 treatments and five repetitions. The results showed that Corn seed media gave the maximum mycelium growth results compared to Sesame and Winged Bean seed media. The research data were then analyzed statistically using One Way Anova and Tukey HSD tests. The results of One Way Anova analysis showed that the average value of P. ostreatus mycelium growth between groups of nursery media was significantly different. The results of the Tukey HSD analysis showed that there was no significant difference between the nursery media between Sesame seeds and Winged Bean seeds, while Corn with sesame and winged bean seeds had significant differences.